Oxidative stress, lysosomal damage and dysfunctional autophagy in molluscan hepatopancreas (digestive gland) induced by chemical contaminants. (December 2019) - Shaw, J.P.; Moore, M.N.; Readman, J.W.; Mou, Z.; Langston, W.J.; Lowe, D.M.; Frickers, P.E.; Al-Moosawi, L.; Pascoe, C.; Beesley, A.
Abstract: Autophagy is a highly conserved evolutionary survival or defence process that enables cells and organisms to survive periods of environmental stress by breaking down cellular organelles and macromolecules in autolysosomes to provide a supply of nutrients for cell maintenance. However, autophagy is also a part of normal cellular physiology that facilitates the turnover of cellular constituents under normal conditions: it can be readily augmented by mild environmental stress; but becomes dysfunctional with severe oxidative stress leading to cellular pathology. The molluscan hepatopancreas or digestive gland provides a versatile and environmentally relevant model to investigate lysosomal autophagy and stress-induced dysfunctional autophagy. This latter process has been implicated in many animal and human disease conditions, including degenerative and neurodegenerative diseases, as well as obesity related conditions. Many environmental pollutants have also been found to induce dysfunctional autophagy in molluscan hepatopancreatic digestive cells, and in this study, the marine blue mussel Mytilus galloprovincialis was exposed for 7 days to: 0.1 μM, 1 μM and 10 μM concentrations of fluoranthene and phenanthrene (PAHs); chlorpyrifos and malathion (organophosphorus compounds); atrazine (triazine herbicide); copper (transition metal) and dodecylbenzene sulphonic acid (LAS, surfactant). The marine snail or periwinkle, Littorina littorea, was also exposed to phenanthrene, chlorpyrifos and copper. Indices of oxidative stress, cell injury and dysfunctional autophagy were measured (i.e., lysosomal membrane stability, protein carbonyls, lipofuscin, and lysosomal accumulation of lipid or lipidosis). Evidence of oxidative stress, based on the elevation of lipofuscin and protein carbonyls, was found for all compounds tested; with chlorpyrifos being the most toxic to both species. Dysfunctional autophagy was induced by all of the compounds tested in both species, except for atrazine in mussels. This failure of normal autophagy was consistently associated with oxidative stress. Autophagic dysfunction is an important emerging feature in the aetiology of many disease conditions in animals and humans; and an explanatory conceptual mechanistic model has been developed for dysregulation of autophagy in response to oxidative stress. Highlights: Dysfunctional autophagy as a pathological reaction to chemically induced stress appears to be a widespread phenomenon. Dysfunctional autophagy is characteristic of a number of animal and human diseases, including neurodegenerative diseases. Some of these disease conditions have been linked to uptake of harmful nanoscale materials derived from road traffic. Abstract : Oxidative stress was induced by a range of contaminants in two marine molluscs resulting in dysfunctional lysosomal autophagy in digestive gland cells.